Proteína 1 de merozoíto de Plasmodium vivax: estudo da resposta imune específica contra domínios polimórficos e conservados em populações brasileiras - Cristiane Guimaraes Morais (2011)
Most studies regarding the role of Plasmodium vivax MSP-1 (PvMSP1) in protective immunity against malaria have focused on C-terminal conserved region of molecule. However, there are convincing evidences suggesting the polymorphic sequences of MSP-1, which are under balancing selection, as target of protective immune response. Despite this evidence, our current knowledge regarding the naturally acquired antibody responses against the polymorphic domains of PvMSP-1 is very limited. Here, we evaluated the IgG response directed against conserved (MSP119) and polymorphic (block 2 and 10) epitopes of PvMSP-1 in 214 patients with clinical malaria, only infected by P. vivax, living in Brazilian endemic area. Ten recombinant proteins corresponding to allelic variants of blocks 2 (variants BR07, BP29, BP39, BP30, BEL) and 10 (BR07, BP29, BP39, BP01, BP13) of PvMSP-1 commonly found in Brazilian P. vivax isolates were expressed in Escherichia coli, in addition to a recombinant corresponding to the conserved 19-kDa C-terminal subunit of PvMSP-1, the MSP119 protein. Our data show that the most of recombinant proteins corresponding to PvMSP-1 variants were poorly recognized (13-31%) by serum of individuals evaluated; with exception of responses detected for BR07 and BP13 variants, which recognition by IgG antibodies was higher than 40%. Regarding the magnitude of the variant-specific response, the average of IgG levels were also low, with the highest reactivity detected for antibodies against the variants BR07 and BP13. Unlike the response pattern observed for polymorphic epitopes, 89% of individuals had IgG against the C-terminal conserved domain (MSP119), confirming the high immunogenicity of this region of the molecule. Proportion and levels of antibodies to BP13 variant of block 10 and to MSP119 were associated with exposure to malaria (number of previous clinical episodes), suggesting that during an acute P. vivax infection, there is a boosting in antibody response directed against these C-termini PvMSP-1 epitopes. An important but that remains poorly investigated in P. vivax infections is the association of clinical parameters of morbidity, such as anemia and thrombocytopenia and allele-specific antibody response to P. vivax antigens. By using a combination of statistical analyses that employed univariate and multivariate approaches (PCA); we showed negative correlations between levels of hemoglobin and IgG antibodies against BR07 and BP13 versions of block 10 (Spearman correlation test, P < 0.0001). Interestingly, the sequences of these variants were identified in higher prevalence in infecting parasites from anemic patients when compared to non-anemic; showing that the specificity of IgG antibodies matched the block 10 PvMSP-1 variant found in infecting parasites. These data suggest the possible involvement of IgG to allelic-specific epitope of infecting variant form and targeted to polymorphic C-terminal region of PvMSP-1 in the immunological mechanisms that have been implicated in aetiology of malarial anemia by P. vivax. Overall, our results show a distinct pattern of immune recognition, in terms of variant-specific antibodies, between N- and C-termini PvMSP-1 domains. These findings may have implications for PvMSP-1 -based vaccine development and highlight the real need to expand the studies on the immune response directed against polymorphic epitopes of PvMSP-1 in different epidemiological situations.